Underweight in Child Aged 24-59 Months in North Sumatra: the 2014 Indonesia Family Life Survey Data - Salsabila Kurnianingtyas; Ratu Ayu Dewi Sartika; Winda Mulia Ningsih (Indonesian Journal of Public Health Nutrition, 2021)
AbstractUnderweight has the biggest risk against burden of disease. The aim of the study was to determine the factors related with underweight in child aged 24-59 months lived in North Sumatra based on three characteristics caused an underweight; there are child characteristics, maternal characteristics, and parenting characteristics. This study used cross-sectional design and using chi-square statistical analysis. The sample used in this study was 280 child aged 24-59 months living in North Sumatra province, Indonesia. The data was obtained from 2014 Indonesian Family Life Survey collected by RAND Corporation. Prevalence of underweight in child aged 24-59 months lived in North Sumatra was 26% (Girls: 32,6%, Boys: 19,9%). The statistical analyses found that female child (OR 95% CI= 0,514: p=0,02), maternal low body mass index (OR 95% CI = 3,750: p=0,04) and cigarette expenditure (OR 95% CI = 1,800: p=0,040) contribute to underweight child aged 24-59 month in North Sumatra province. Child gender, maternal body mass index, and cigarette expenditure were the significant determinants for underweight in under-five children in North Sumatra. The intervention is necessary to be implemented by all parties to decrease the prevalence of underweight.AbstrakBerat badan kurang (underweight) memberikan risiko terbesar terhadap beban penyakit. Tujuan penelitian ini adalah mengetahui faktor yang berhubungan dengan kejadian underweight pada anak usia 24-59 bulan di Provinsi Sumatra Utara berdasarkan dengan tiga karakteristik, yakni karakteristik anak, ibu, dan pola asuh. Penelitian ini menggunakan desain studi potong lintang dan menggunakan analisis chi-square. Jumlah sampel yang digunakan sebanyak 280 anak berusia 24-59 bulan dan berdomisili di Sumatra Utara. Data yang digunakan berasal dari data Indonesia Family Life Survey tahun 2014 yang dikelola oleh RAND Corporation. Prevalensi kejadian underweight pada anak usia 24-59 bulan di Sumatra Utara sebesar 26% (perempuan: 32,6%, laki-laki: 19,9%). Analisis statistik menyatakan bahwa jenis kelamin perempuan (OR 95% CI= 0,514: p=0,02), indeks massa tubuh ibu yang rendah (OR 95% CI = 3,750: p=0,04) dan pengeluaran untuk rokok (OR 95% CI = 1,800: p=0,040) berkontribusi terhadap kejadian underweight pada anak usia 24-59 buan di Sumatra Utara. Jenis kelamin anak, indeks massa tubuh ibu, dan pengeluaran rokok merupakan faktor yang signifikan terhadap kejadian underweight pada anak usia di bawah lima tahun di Provinsi Sumatra Utara. Langkah intervensi diperlukan untuk dapat diimplementasikan oleh seluruh masyarakat untuk dapat menurunkan prevalensi kejadian underweight.